Histological and Growth response of Clarias gariepinus fish seeds raised on unprocessed dried leaves of Telfairia occidentalis and Mucuna utilis - Adebola Oluyinka Ajiboye; Adenike Susannah Tola-Fabunmi; Abolupe Oluyemi Ayanboye (Aceh Journal of Animal Science, 2022)
Nutrient utilization is determined by absorbable and digestible nutrients in fish feeds. Sixteen weeks feeding trial experiment was conducted using two hundred and twenty-five Clarias gariepinus of mean weight 4.16±0.09g. The aim of the experiment was to investigate the effects of unprocessed dried leaves of Telfairia occidentalis (UDLTO) and Mucuna utilis (UDLMU) on histology and growth of C. gariepinus.  Fish meal was replaced with 0%, 25%, 50%, 75% and 100% levels of UDLMU and UDLTO. Growth parameters and histological examinations were carried out according to standard procedures. Data obtained were subjected to ANOVA and Duncan Multiple Range Test was used to separate the means. MWG of T1 (15.8g) was significantly higher P0.05 compared to other treatments. SGR of T1 (0.64) varied significantly P0.05 than other level of inclusions. Kidneys of fish fed 25% and 50% graded levels showed patchy vacuolar degeneration of the renal tubules. Gills of fish fed 75% and 100% graded levels showed diffuse capillaries and moderate congestion of lamellar in the gills. Tissue examinations of fish fed 50%, 75% and 100% graded levels exhibited clinical signs of moderate atrophy and vacuolation of hepatocytes and diffuse hepatocellular swelling and degeneration in the liver. Histological investigations revealed fragmentation and atrophy of muscle fibre in fish fed 75% graded level. There was moderate atrophy of villi of intestine of fish fed 100% graded level.It is apparent that increased level of UDLMU and UDLTO could not support good growth as presumed due to presence of anti-nutritional factors in the leaves.Key: Nutrient utilization, Fish meal, Inclusions, standard procedures, Clinical signs